Технології sika для реконструкції мостів - Собко, Ю. М.; Панченко, О. В.; Сінякін, А. Г.; Тарнопольський, Д. Й.; Вітрук, В. М.; Кот, О. В.; Войцехівський, О. В.; Байда, Д. М.; Sobko, Yu.; Panchenko, O.; Sinyakin, A.; Tarnopolskij, D.; et al. (Видавництво Львівської політехніки, 2018)
У статті подано опис варіантів реконструкції і розширення габариту проїзду, підсилення і захист конструкцій шляхопроводів на перетині просп. Науки і магістральної вулиці, на перетині вул. Д. Щербаківського з просп. Перемоги, шляхопроводу на Одеській площі у м. Києві, та моста через Пд. Буг у м. Вінниці за технологіями Sika, що дозволило перевести споруди у дискретний стан 1 [3].

The article describes the static scheme and the construction of bridge superstructure overpasses at the interchange of the Nauky Prospectus and the main line of the continuous traffic highway and at the interchange of the Danylo Shcherbakivsky Street from Peremogy Prospectus near Metro Station “Nyvky”, overpass in the Odessa Square in Kyiv and the bridge across the Southern Bug River in Vinnytsia City. The results of the inspection of structural elements of the bridge structures technical condition was also described, and bridges operational state according to the VBN classification were determined. As a result of the analysis, the repair strategy and variants of reconstruction with traffic gabarite and sidewalks widening were determined including the replacement of the bridge deck plate and the design of strengthening system by SikaCarboDur CFRP materials were developed. The technology of RC structures repair and protection using the technologies of SikaMonotop and Sikagard are given. As a result, that allowed us to carry out chosen repair strategy and reconstruction, to do strengthening, repair and protection of RC elements at a high technical level and in the planned short time of construction, to transfer bridge superstructures to the discrete state category 1 [4] and extend the Life Cycle Time.
Sika technologies for bridges reconstruction
Keywords: обстеження; ремонт бетону; підсилення вуглепластиками; bridge beam; concrete repair; CFRP strengthening; concrete protection; 624.21; 69.05